2022
DOI: 10.3390/cancers14051196
|View full text |Cite
|
Sign up to set email alerts
|

Biglycan Interacts with Type I Insulin-like Receptor (IGF-IR) Signaling Pathway to Regulate Osteosarcoma Cell Growth and Response to Chemotherapy

Abstract: Osteosarcoma (OS) is a mesenchymally derived, aggressive bone cancer. OS cells produce an aberrant nonmineralized or partly mineralized extracellular matrix (ECM) whose components participate in signaling pathways connected to specific pathogenic phenotypes of this bone cancer. The expression of biglycan (BGN), a secreted small leucine-rich proteoglycan (SLRP), is correlated to aggressive OS phenotype and resistance to chemotherapy. A constitutive signaling of IGF-IR signaling input in sarcoma progression has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 92 publications
(137 reference statements)
0
13
0
Order By: Relevance
“…The details of all signaling pathway networks identified were also shown in Figures 6A-C (A: numbers of ligand receptors among all cell types; B: weights of ligand receptors among all cell types; C: chordal graph of ligand-receptor interactions among all cell types). Among the total of 57 signaling pathways, the following signaling pathways were related to osteosarcoma: COLLAGEN ( Baumann and Hennet, 2016 ; Elenjord et al, 2009 ; Levinson et al, 2002 ; Yamaguchi et al, 2005 ), CD99 ( Manara et al, 2006 ; Sciandra et al, 2014 ; Zucchini et al, 2014 ), PTN ( He et al, 2019 ; Qin et al, 2022 ; Sun et al, 2020 ), MIF( Liu et al, 2014 ), SPP1( Dalla-Torre et al, 2006 ; Li et al, 2017 ), FN1( Saba et al, 2019 ; Zhou et al, 2019 ), LAMININ( Heino and Massague, 1989 ), FGF ( Kurogi et al, 1996 ; Laulederkind et al, 2000 ; Li et al, 2019 ; Xu et al, 2010 ), VEGF ( Ji et al, 2020 ; Lei et al, 2018 ; Oda et al, 2006 ; Tsai et al, 2017 ; Zhang et al, 2019 ), GALECTIN( Gomez-Brouchet et al, 2010 ; Miao et al, 2014 ; Park et al, 2015 ; Zhou et al, 2014 ), PERIOSTIN( Ma et al, 2020 ; Xu et al, 2022 ), VISFATIN( Cheng et al, 2015 ; Wang et al, 2019 , 2016 ), ITGB2 ( Dai et al, 2018 ), NOTCH( Jin et al, 2017 ; Mu et al, 2013 ; Ongaro et al, 2016 ; Tanaka et al, 2009 ; Zhang et al, 2010 ), IGF ( Armakolas et al, 2016 ; Giatagana et al, 2022 ; Gvozdenovic et al, 2017 ; Molina et al, 2019 ; Tan et al, 2015 ), VWF( Wang et al, 2020 ), and PDGF ( Chen et al, 2009 ; Egners et al, 2018 ; Heldin et al, 1986 ). The ligand-receptor interact...…”
Section: Resultsmentioning
confidence: 99%
“…The details of all signaling pathway networks identified were also shown in Figures 6A-C (A: numbers of ligand receptors among all cell types; B: weights of ligand receptors among all cell types; C: chordal graph of ligand-receptor interactions among all cell types). Among the total of 57 signaling pathways, the following signaling pathways were related to osteosarcoma: COLLAGEN ( Baumann and Hennet, 2016 ; Elenjord et al, 2009 ; Levinson et al, 2002 ; Yamaguchi et al, 2005 ), CD99 ( Manara et al, 2006 ; Sciandra et al, 2014 ; Zucchini et al, 2014 ), PTN ( He et al, 2019 ; Qin et al, 2022 ; Sun et al, 2020 ), MIF( Liu et al, 2014 ), SPP1( Dalla-Torre et al, 2006 ; Li et al, 2017 ), FN1( Saba et al, 2019 ; Zhou et al, 2019 ), LAMININ( Heino and Massague, 1989 ), FGF ( Kurogi et al, 1996 ; Laulederkind et al, 2000 ; Li et al, 2019 ; Xu et al, 2010 ), VEGF ( Ji et al, 2020 ; Lei et al, 2018 ; Oda et al, 2006 ; Tsai et al, 2017 ; Zhang et al, 2019 ), GALECTIN( Gomez-Brouchet et al, 2010 ; Miao et al, 2014 ; Park et al, 2015 ; Zhou et al, 2014 ), PERIOSTIN( Ma et al, 2020 ; Xu et al, 2022 ), VISFATIN( Cheng et al, 2015 ; Wang et al, 2019 , 2016 ), ITGB2 ( Dai et al, 2018 ), NOTCH( Jin et al, 2017 ; Mu et al, 2013 ; Ongaro et al, 2016 ; Tanaka et al, 2009 ; Zhang et al, 2010 ), IGF ( Armakolas et al, 2016 ; Giatagana et al, 2022 ; Gvozdenovic et al, 2017 ; Molina et al, 2019 ; Tan et al, 2015 ), VWF( Wang et al, 2020 ), and PDGF ( Chen et al, 2009 ; Egners et al, 2018 ; Heldin et al, 1986 ). The ligand-receptor interact...…”
Section: Resultsmentioning
confidence: 99%
“…Studies examining the variabilities in the protein core and glycosylation patterns have described 45 different PGs [16]. However, the localization of secreted and cell membrane PGs can be changed due to alterations in synthesis/endocytosis or shedding [25,35]. The expression of PGs, their ECM, and cellular and specific subcellular localization varies between cancer types, thus modulating cell function and tumor differentiation [1,6].…”
Section: The Tumor Ecmmentioning
confidence: 99%
“…Finally, as discussed in bone tissue, SLRPs, by binding a plethora of cell membrane receptors, growth factors, and cytokines, can initiate and regulate specific intracellular signaling, thereby modulating cell functions [53]. Notably, a multitude of studies have shown that SLRPs' interaction with tyrosine kinase receptors or growth factors regulates biological functions and tumor progression [23][24][25][26]. In addition, SLRPs can be secreted upon tissue insult, bind toll-like receptors (TLRs), and take on the role of damage-associated molecular patterns [27].…”
Section: Slrps Structure and Rolesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the small leucine-rich repeat proteoglycan of bone extracellular matrix tissue biglycan, which is correlated with an aggressive phenotype of osteosarcoma, supported tumor growth and induced resistance to chemotherapy drug doxorubicin by forming a complex with IGF-1R leading to activation of the IGF-1R signaling pathway in human osteosarcoma cell line MG63 ( 37 ). Similarly, miR-520b promoted doxorubicin sensitivity in breast cancer cells through downregulation of IGF-1R, i.e., abrogating tumor development, metastasis, and resistance to chemotherapy induced by IGF-1R ( 38 ).…”
Section: Tumor Microenvironment Tumorigenesis and Drug Resistancementioning
confidence: 99%